Faktor-Faktor Yang Mempengaruhi Kejadian Nyeri Punggung Bawah (Low Back Pain) Pada Pekerja Pengemudi - Yohana Prima Dewi Yustika Rini; Agustina Sri Oktri Hastuti; Avin Maria (STIKes Panti Rapih, 2022)
Background: Low back pain is a disease that is felt mostly by those who do their work both statically and dynamically, lack doing some exercises, take a long seat, and bend over too long. Examples of this are drivers. They work long hours daily with lots of passengers and goods. As a result, they are forced to be seated in a long time with static position and sometimes they apply improper sitting position. In addition, there are several factors causing them to have a low back pain, i.e. IMT or BMI, work period, sitting position, work duration, exercise, smoking, and age as well. Objective: This literature review is aimed at finding out factors that result in low back pain happening to drivers. Method: The method of this literature review is scoping review. The articles for this literature review are collected from several database comprising Google scholar, PubMed, Proquest, Wiley online library and The Cochrane Collaboration.The articles selected are the ones published between 2016 and 2021. The article analysis and sifting uses the method PRISMA. Results: Six articles were found to be appropriately used and they are in line with the criterion of both inclusion and exclusion. As many as 66.67% of the articles discuss sitting position, 50% discuss work duration, 66.67% discuss age factor, 50% discuss IMT, 83.33% discuss work period, 100% discuss exercises, and 83.33% discuss smoking. Conclusion: The factors of sitting position, work duration, age, exercise, and smoking contribute to low back pain that happens to drivers. Meanwhile, the factors of IMT or BMI and work period are not associated with low back pain in drivers. Keywords: factors, low back pain, driver